Legal and financial aspects of the widow’s pension with particular emphasis on social insurance for farmers - Puślecki, Damian (Przegląd Prawa Rolnego, 2025)
This study aims to evaluate the legal and financial conditions for the functioning of the surviving spouse’s pension in the context of compensating for lost income in the household following the death of a spouse. This issue is particularly important to farmers who currently receive some of the lowest pension benefits in Poland. The author argues that the introduced regulation, with the currently established 15% rate of the second benefit, does little to fulfil the compensatory and security functions of social insurance. The surviving spouse’s pension is not a new benefit, but rather a complex legal construct that enables the beneficiary to retain the entitlement to a benefit that coincides with the equivalent to the alternative of choosing a higher benefit. Considering the financial aspects and the established limits, the new solution can only serve as an additional measure for the beneficiaries of the Social Insurance Institution (ZUS) and the Agricultural Social Insurance Fund (KRUS) which significantly deviates from the principle of social justice or the models adopted in the analysed EU countries.